RELATIONSHIP BETWEEN TOTAL QUALITY MANAGEMENT ELEMENT, OPERATIONAL PERFORMANCE AND ORGANIZATIONAL PERFORMANCE IN FOOD PRODUCTION SMEs - Sutrisno, Timotius F. C. W. (Universitas Brawijaya, Indonesia, 2019)
The system of improvement and quality management has a fairly rapid development to answer the needs of consumers in the future. TQM is a solution to improve quality in the SMEs food industry, which contributes greatly to the developing countries. The purpose of this paper is to explore the relationship between TQM elements consisting of Soft and Hard aspects, for operational performance and their impact on the performance of SME organizations. Empirical data was taken from 136 SMEs in food production in the East Java Region of the Republic of Indonesia. This study uses Confirmatory Factor Analysis to test construct reliability and validity, while the relationship between variables is examined through Partial Least Square. This research proves that improving operational performance is influenced by the element Soft and Hard TQM and organizational performance achievement is influenced by operational performance. The fact that this research is based on the quality perspective of SME owners of food production and is expected to have an impact on future research on operational management in SMEs. To achieve benefits and obtain sustainable competitive advantages for companies at the SME level, Hard TQM and Soft TQM are not enough, a quality-oriented organizational culture is needed to solve them.